Probabilistic-based structural safety analysis of concrete dams - PhD thesis work plan of Renato Pereira - Pereira, R. (2016)
The construction and operation of dams, associated with the use of water resources, aim generically at the energy producing, water supplying and, in some cases, flow regulating and flood controlling. Considering the dam dimensions and the potential risks associated with its collapse, due to the occupation of the downstream valley, and to the costs of the construction, maintenance and rehabilitation, the use of probabilistic principles in its design, as it is already performed for other type of structures, is justified. With this thesis work plan, it is intended to establish a methodology for the structural safety analysis of concrete dams based on the definition of safety evaluation criteria, considering the partial safety factors obtained through structural reliability analysis. For that purpose, the uncertainties involved in the safety of concrete dams shall be statistically quantified, through the definition of probabilistic distributions for loads and material properties, using, in addition to the elements found in the literature, the information available at LNEC about those features, resulting from the monitoring of the concrete dam behavior during the construction, first filling and operation periods. Later, the partial safety factors shall be calibrated analysing the outcomes of the structural reliability analysis performed to models of concrete dams, representative of the standard solutions for different design situations. It is expected that this work contributes to the discussion on the design criteria of concrete dams and can be integrated into future revisions of the Portuguese dam safety regulation.